Tinjauan Hukum Sertifikat Halal pada Produk Pangan Impor di Indonesia: Legal Review of Halal Certification for Imported Food Products in Indonesia - Mohammad Hangga Afandi; Tuti Herningtyas; Rommy Hardyansah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Food and its processed products are a vital basic human need. Given that the majority of Indonesia's population is Muslim, compliance with strict regulations regarding food types and halal requirements is mandatory in food selection. The purpose of this study is to emphasize the importance of a clear legal status and a strong legal framework for halal certification within the national legal system. This research method uses a legal approach, which aims to answer various legal questions, both academically and practically, covering legal principles, applicable legal norms, and the implementation of existing laws. Data collection techniques include cataloging and determining the identity of laws and regulations, as well as systematically grouping and organizing legal materials according to the research objectives, so that the collected legal materials can be properly organized. The results of the study indicate that this is crucial for protecting Muslim consumers and ensuring food meets halal standards. Law Number 8 of 1999 concerning Consumer Protection also emphasizes the importance of product safety for consumers. This study analyzes the legal aspects of halal certification for imported food products in Indonesia, identifies challenges in its implementation, and provides recommendations for improving the effectiveness of supervision and law enforcement related to halal certification.